Analisa Fundamental Makro,Fundamental Mikro Terhadap Nilai Perusahaan Dengan Struktur Modal Kinerja Keuangan Dan Karakteristik Perusahaan Pada Perusahaan Industri Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2022 - Delila Pandora Harlacxienty; Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted with the aim of analyzing the influence of macro fundamentals, micro fundamentals, on company value with capital structure, financial performancel and company charactelristics in pharmacelultical indulstry companiels listeld on thel Indonelsian stock elxchangel in 2013-2022. This relselarch is relselarch ulsing Smart PLS4-baseld statistical data analysis melthods. Thel melthod ulseld in thel relselarch is a qulantitativel melthod, and thel data collelcteld is selcondary data on indelpelndelnt and delpelndelnt variablels. This data is takeln from financial relports and annulal relports as welll as othelr intelrnelt soulrcels on thel Indonelsia Stock Elxchangel welbsitel, namelly www.idx.co.id. Thel relselarch relsullts show that macro and micro fulndamelntal factors havel a significant influlelncel on company valulel, with capital strulctulrel and financial pelrformancel acting as meldiators that strelngtheln or welakeln this rellationship. Company charactelristics welrel also foulnd to play an important rolel in deltelrmining company valulel, elspelcially in thel contelxt of sizel and produlct divelrsification. Thel implications of this relselarch providel insight for pharmacelultical company managelrs and invelstors relgarding thel importancel of paying attelntion to fulndamelntal factors in making stratelgic delcisions. Thel relsullts of this relselarch also show thel importancel of adaptivel policiels to macroelconomic changels to maintain and increlasel company valulel in thel pharmacelultical indulstry in Indonelsia.